Assessment of drilling water quality at Tan Thanh commune, Thanh Binh district, Dong Thap province - Phạm Thị Hồng Vân (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kỹ thuật và Công nghệ, 2019)
Water from drilled wells is one of the water sources that play a very important role in providing clean water to people in Tan Thanh commune, Thanh Binh district, Dong Thap province. In this article, the author analyzed water samples and compared them with the Vietnamese standard QCVN 09MT: 2015/BTNMT to assess groundwater quality. The results of the analysis of water samples from drilled wells show that the values of pH, nitrate, sulphate and chloride are within the permitted standards (Bộ trưởng Bộ Tài nguyên và Môi trường, 2015); Total Fe content ranges from 1.59 to 2.50 mg/L and turbidity of about 9.1-26.3 NTU exceeds the permissible limit of the living water (QCVN 02-2009-BYT iron is 0, 5 mg/L and turbidity less than 5 NTU) (Cục Y tế dự phòng và Môi trường, 2009). Therefore, it is necessary to carry out the treatment of iron content in water before use.